2014
DOI: 10.1097/jcp.0b013e3182a607dd
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Patterns of Antipsychotic Use in Youth at the Time of Admission and Discharge From an Inpatient Psychiatric Facility

Abstract: The objective of this study was to examine the prevalence and patterns of antipsychotic use in children and adolescents at the time of admission and discharge from a tertiary care inpatient psychiatric facility. This retrospective analysis included all patients 18 years and younger, who were admitted and discharged from a child and adolescent tertiary care inpatient psychiatric facility between May 1, 2008 and December 31, 2009. Data for medications at admission were obtained using a province-wide network that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
(11 reference statements)
0
13
0
1
Order By: Relevance
“…First, this may be the period of most rapid physical change, particularly as patients are starting from a healthier baseline and some may have not yet reached full sexual maturity (33). Second, patients have less of a “history” with previous antipsychotic medications, and are less likely to be treated with multiple antipsychotic drugs or additional classes of psychotherapeutic medications (20), meaning that observed physical changes can be interpreted with greater clarity. Finally, the greater receptivity of patients and family during this phase of the illness (6) is conducive to engaging the patients in the type of longitudinal research studies that will ultimately be necessary for progress to be made in understanding these issues.…”
Section: Health-related Research At the Vancouver/richmond Early Psycmentioning
confidence: 99%
See 1 more Smart Citation
“…First, this may be the period of most rapid physical change, particularly as patients are starting from a healthier baseline and some may have not yet reached full sexual maturity (33). Second, patients have less of a “history” with previous antipsychotic medications, and are less likely to be treated with multiple antipsychotic drugs or additional classes of psychotherapeutic medications (20), meaning that observed physical changes can be interpreted with greater clarity. Finally, the greater receptivity of patients and family during this phase of the illness (6) is conducive to engaging the patients in the type of longitudinal research studies that will ultimately be necessary for progress to be made in understanding these issues.…”
Section: Health-related Research At the Vancouver/richmond Early Psycmentioning
confidence: 99%
“…However, an additional factor that has been the focus of considerable research over the past decade is the direct cardiometabolic effects of the antipsychotic drugs themselves (16–19). Antipsychotic drugs can be given for a wide range of different psychiatric indications, in both adults and youth (20–23). …”
Section: Introductionmentioning
confidence: 99%
“…The problem is more pronounced for hospitalized patients who received a higher number of psychotropic medications than in the community. Several studies conducted since 1976 have evaluated the prescription of these drugs in children and/or adolescents in psychiatric wards in the USA (Zito et al 1994;Kaplan and Busner 1997;Safer 1997;Pappadopulos et al 2002;Kelly et al 2004;Lekhwani et al 2004;Najjar et al 2004;Pathak et al 2004;Pogge et al 2007;Meagher et al 2013;Saldana et al 2014), Canada (Ahsanuddin et al 1983;Procyshyn et al 2014), Finland (Sourander et al 2002;Haapasalo-Pesu et al 2004), France (Winterfeld et al 2008;Consoli et al 2009), United Kingdom (Akram 2015), Serbia (Pejovic-Milovancevic et al 2011), Israel (Gilat et al 2011), Australia (Dean et al 2006) and China (Song and Guo 2013). The proportion of patients treated with psychotropic medication was high, ranging from 30% to 100%.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relative important number of studies, the majority have some limitations such as the evaluation of a single prevalence period (Ahsanuddin et al 1983;Zito et al 1994;Kaplan and Busner 1997;Pappadopulos et al 2002;Sourander et al 2002;Kelly et al 2004;Lekhwani et al 2004;Pathak et al 2004;Dean et al 2006;Pogge et al 2007;Winterfeld et al 2008;Consoli et al 2009;Pejovic-Milovancevic et al 2011;Procyshyn et al 2014;Saldana et al 2014;Akram 2015), the analysis of prescriptions at a single point during hospitalization (Sourander et al 2002;Haapasalo-Pesu et al 2004) or at admission and/or discharge only (Safer 1997;Lekhwani et al 2004;Gilat et al 2011;Meagher et al 2013;Procyshyn et al 2014;Saldana et al 2014;Akram 2015), the study of antipsychotics only (Pappadopulos et al 2002;Kelly et al 2004;Pogge et al 2007;Procyshyn et al 2014;Saldana et al 2014), or the inclusion of children only (Lekhwani et al 2004;Pathak et al 2004;Akram 5/23 2015). The rate of off-label prescriptions was evaluated in only three of these studies, at a single prevalence period (Winterfeld et al 2008;Procyshyn et al 2014;Akram 2015), at admission and discharge for antipsychotics (Procyshyn et al 2014), and at discharge for ch...…”
Section: Introductionmentioning
confidence: 99%
“…1 Our group has also reported that 25% of children discharged on an antipsychotic from the Child and Adolescent Mental Health Inpatient Program at BC Children's Hospital were coprescribed a psychostimulant. 2 As monotherapy, both psychostimulants and antipsychotics are supported by a reasonable amount of evidence for the treatment of ADHD and disruptive behaviour disorders. On first impression, the combination of a psychostimulant and antipsychotic, with their opposing effects on dopamine (DA) neurotransmission, (i.e., indirect agonist v. antag onist) seems contradictory and illogic al.…”
mentioning
confidence: 99%